Effluent from Citrus Industry: Toxic Parameters of Orange Vinasse - Garcia, Camila Fernandes H. [UNESP]; de Souza, Raphael B. [UNESP]; de Souza, Cleiton Pereira [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Springer Nature, 2019)
Brazil is one of the greatest producers of orange and its orange juice processing industry produces large volumes of solid and liquid waste daily. As an efficient use of the residues from citrus industry, production of bioethanol is highlighted. However, the generation of bioethanol produces a liquid effluent as a by-product, known as vinasse. The objective of this study was to evaluate the toxicity of an effluent from citrus industries, orange vinasse, when applied to soil using Allium cepa seeds. The evaluation was performed by means of germination, root growth, and genotoxic and mutagenic parameters. The EC50 (effectiveness concentration) and ½ EC50, defined in the germination test, were used for genotoxicity tests. Toxicity was observed in dilutions above 40%, which was responsible for reducing the germination speed index. Genotoxicity was observed only using the EC50 and mutagenicity was not detected. According to the results, orange vinasse showed toxicity similar to the sugar cane vinasse, so caution is suggested in the disposal of this effluent into the environment.
Keywords: Chromosomal aberration; Citrus stillage; Genotoxicity; Micronuclei; Phytotoxicity